1992
DOI: 10.1111/j.1532-5415.1992.tb02109.x
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Skilled Cardiopulmonary Resuscitation in a Long‐Term‐Care Facility: Futile Therapy?

Abstract: We conclude that cardiopulmonary resuscitation, even when performed by a trained and experienced physician and team, has limited benefit for elderly long-term-care populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
2

Year Published

1992
1992
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(48 citation statements)
references
References 9 publications
3
43
2
Order By: Relevance
“…Furthermore, the factors of nursing home residency [19,20,30,32,38] and pre-arrest comorbidity [27] were associated with decreased chances of survival. It was striking that only one study investigated the predictive value of pre-arrest comorbidity [27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the factors of nursing home residency [19,20,30,32,38] and pre-arrest comorbidity [27] were associated with decreased chances of survival. It was striking that only one study investigated the predictive value of pre-arrest comorbidity [27].…”
Section: Discussionmentioning
confidence: 99%
“…However, this study did not adjust for arrest factors and only examined witnessed arrests. Of the 23 included studies, six studies investigated the predictive value of nursing home residency for decreased survival to discharge [17,19,20,30,32,38] (Table 3). For this group, the absolute survival chances were low and ranged from 0–5.1%.…”
Section: Findings Of the Included Studiesmentioning
confidence: 99%
“…Both of these indicators suggest reasonably severe levels of impairment in physical functioning and these may be relatively more important for subjective evaluations of quality of life than impairments in mobility, for example. Moreover, patients with relatively severe chronic disease rarely survive to hospital discharge after CPR and this intervention may therefore be viewed as relatively futile (Awoke, Mouton, & Parrott, 1992;Fisher, 1989;Murphy, 1988). However, it should also be recognized that, to some extent the problems associated with conditions such as incontinence may be modifiable.…”
Section: Discussionmentioning
confidence: 95%
“…4 Cardiopulmonary resuscitation is largely irrelevant in the nursing home (it is effective less than 1% of the time when trained personnel are available and the vast majority of nursing homes are not equipped to provide advanced life support). 5 Moreover, DNR continues to be widely misunderstood and is misconstrued to indicate much more than "do not attempt cardiopulmonary resuscitation (CPR)." A recent study confirmed earlier findings that DNR is often interpreted to imply limitations on treatments, such as intensive care, surgery, dialysis, transfusions, and endoscopy.…”
Section: The Current Status Of Advance Medical Planning In Nursing Homesmentioning
confidence: 99%